Linking Sustainable Project Management with Construction Project Success: Moderating Influence of Stakeholder Engagement - Shih-Wei Wu; Yifan Yan; Jialiang Pan; Kun-Shan Wu (Buildings, 2023)
Stakeholder engagement (SE) is an important factor in making a project successful. Steered by the resource-based value (RBV) and stakeholder theories, this paper aims to explore not only the correlation between sustainable project management (SPM) and sustainable project success (SPS), but also the moderating effect of SE on this connection. Data was gathered from 365 questionnaires distributed to construction project professionals in China. Structural equation modelling was employed to test the proposed hypotheses. The results confirm that both SPM and SE positively affect SPS, but the positive moderating effects of SE were found to be insignificant. This article provides the basis for the Chinese construction industry to determine how to achieve SPS through the enhanced implementation of SPM and effective SE.